PERAN ORANG TUA DAN GURU DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA MA DI MASA PANDEMI COVID-19 - Saharudin (Dahzain Nur, 2022)
Abstract This research is a type of qualitative research. Data collection techniques used are observation, interviews and documentation. The data sources for this study were parents and teachers of class XI IPA MA Muhammadiyah Salaka, Pattallassang District, Takalar Regency. Based on the results of the research conducted, the authors conclude that first, parents have a major role in the education of their children so they must always provide encouragement and motivation to learn to children so that they remain enthusiastic in learning even though learning is online and facilitate the facilities and infrastructure needed by children during the online learning process. a teacher has an important role where the teacher as a motivator must always motivate students to take part in learning even though it is through online learning and provide a learning system that attracts students' attention to take part in online learning during a pandemic. Third, if students' learning motivation decreases, it will affect the value given by the subject teacher, but if students' learning motivation is good and diligent in submitting assignments, they will get good grades from the teacher.